1979
DOI: 10.1677/joe.0.0810299
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Prolactin in Mice With a High Incidence of Mammary Tumours: Evidence for Greater Conversion Into a Non-Immunoassayable Form

Abstract: Monomeric mouse prolactin containing small amounts of 125I-labelled prolactin was administered to adult female mice of a high (C3H/St) and low (C57BL/St) mammary tumour strain. Their endogenous prolactin had been suppressed with 2-bromo-alpha-ergocryptine. The chromatographic profile, on Sephadex G-100, of prolactin in the serum of mice injected with mouse prolactin was compared by direct measurement (radioactivity count) and by radioimmunoassay (RIA) at several intervals after injection. With both methods, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1979
1979
2003
2003

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 20 publications
(24 reference statements)
1
6
0
Order By: Relevance
“…This result is in agreement with data reported by others in rats [13,14], mice [22,23] and humans [4,5,7,12,24,25], bearing in mind the species, sex and physiological state, and treatment differences.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result is in agreement with data reported by others in rats [13,14], mice [22,23] and humans [4,5,7,12,24,25], bearing in mind the species, sex and physiological state, and treatment differences.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, size heter ogeneity of PRL has been observed in serum samples of both humans and experimental animals. Three molecular species have been described, the so-called 'little', 'big' and 'big-big' PRLs (21,000-23,000, 40,000-50,000, and higher than 90,000-100,000 daltons, respectively) [1,4,5,7,[11][12][13][14][22][23][24][25][26]. The biological significance of this heter ogeneity remains uncertain, but differences in biological activity have been reported [4,5], Although in acutely uremic rats [18] rPRL plasma levels do not seem to be affected by uremia in itself, it might occur that the uremic environment could in some way influence the size heterogeneity of the circulating rPRL, affecting the extent to which larger forms of PRL are released by the pituitary into circulation and/or mod ifying the relationship that seems to exist between little and big-big PRLs [11,22],…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that we did not see any single mammary carcinoma in the mice. It is well known that some mouse strains develop mammary tumours more or less spontaneously on aging but evidently this strain was resistant to such a development (Gad et al, 1977;Sinha and Baxter, 1979 induced by total COMT inhibition were seen (Frith et al, 1980;Wolford et al, 1986;Loeb and Quimby, 1999). Also, the levels of catecholamines in plasma were not significantly increased in COMT-deficient mice in spite of high DHPG levels.…”
Section: Discussionmentioning
confidence: 98%
“…Rather, developing mammary tumor in some cases may involve subtle abnormalities in the metabolism of the hormone. Immunoreactive prolactin of several molecular sizes have been found to circulate in the blood (Suh and Frantz, 1974;Sinha and Baxter, 19796). We have observed that mice metabolize aportion of the injected prolactin into a non-immunodetectable form in their circulation, and the hightumor C3H/St strain does so to a greater extent than the low-tumor C57BL/St strain (Sinha and Baxter, 19796).…”
Section: Discussionmentioning
confidence: 97%
“…Immunoreactive prolactin of several molecular sizes have been found to circulate in the blood (Suh and Frantz, 1974;Sinha and Baxter, 19796). We have observed that mice metabolize aportion of the injected prolactin into a non-immunodetectable form in their circulation, and the hightumor C3H/St strain does so to a greater extent than the low-tumor C57BL/St strain (Sinha and Baxter, 19796). In addition, we have discovered a structural variant of prolactin in the mouse pituitary which does not cross-react with an antiserum to the major form of mouse prolactin, the antiserum that is used in our present radioimmunoassay (Sinha and Baxter, 1979~).…”
Section: Discussionmentioning
confidence: 99%